Crisis of modern visual practices - A. I. Tapol, (Ukrainian Cultural Studies, 2019)
The article focuses on the analysis of the liquefaction of basic settings of the modernity's visual practises, specifically of signification regime and mode. The general dynamics of historical types of visual practices and the role of the Modern vision regime in it are described. The visual parameters of the signifying modes of realism and modernism are defined. The crisis of modern visual practices is specified through the logic of their transformation. The status of photography as the basic visual practice of the modernism signifying mode is proved.From the beginning of the era of "technical production" the pathos of the position of the artist as the producer of the image requires not only the act of creation, but also the aim of commercialization, which entails the act of "exhibiting", a certain way of presentation. An important aspect of the artist's mission is to move the image from the everyday and profane (if we resort to aesthetic categorical apparatus) spheres to the space of the artistic field.A striking example of the dilution of the visual parameters of high Modernity is photography. The lens becomes the mediator of the act of seeing the person, and subject-object relations with the world break because of the mediocrity of the photographic image, which promotes its reality.Photo documentation creates a new form of perception of time – fragments in which some events are identified as important and some remain peripheral. If an artist thinks of painting (Cézanne's thought) and has creative thinking, then a photographer who thinks of frames only reduces being to the individual. A photo does not simply reflect reality, it reproduces reality, that is, it transfers it from thing to reproduction of things, photography carries the existence of a photographed object. And as a result, we recognize that the photographic image is the object itself.Photography as an image begins to organize not only high culture, but also everyday life, being the basis of visuality and the basis of everyday social practices. The transformations that photo-images make to the parameters of Modernity's visuals form the basis for visual postmodernism.
Keywords: visual practice , Modernity, signifying mode, realism, modernism, photography